Smart Automation of Salinity and Turbidity for Sustainable Aquaculture of Harpodon nehereus - Prasetia, Abdul Muis; Gazali Salim; Linda Sartika; Mujiyanto Mujiyanto; Julian Ransangan; Ariel E San Jose; Sitti Hartinah; Retno Hartati; Rozi (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abstract   Highlight Research 1. Model of growth and mortality of otek fish (Netuma thalassina (Rüppell, 1837)) in Tarakan waters, North Kalimantan. 2. Growth, mortality, and reproductive model of Bombay duck (Harpodon nehereus, Hamilton 1822) in Juata Laut waters, North Kalimantan. 3. Growth pattern and the condition index of nomei fish Harpodon nehereus captured with mini trawl in Tarakan Waters. 4. Characteristics of Model Growth and Mortality of White Shrimp (Penaeus merguiensis de Man 1888) in The Estuaria of Bengara, Regency Bulungan. 5. Preliminary study on the domestication of giant freshwater prawn, Macrobrachium rosenbergii (De Man, 1879) from North Kalimantan, Indonesia.   Abstract Automated water quality monitoring systems are urgently needed to ensure fish health and maintain aquaculture product quality. This study develops an adaptive microcontroller-based control system that automatically regulates salinity and turbidity to support the sustainable aquaculture of Harpodon nehereus. This study developed and evaluated a microcontroller-based system for automated regulation of salinity and turbidity in H. nehereus aquaculture ponds. Methods involved environmental observation, sensor calibration, system design, and field validation of a digital sensor-based water quality controller, tested in a pilot estuarine pond to keep salinity (~17‰) and turbidity (20-30 NTU) within optimal ranges. Calibration results obtained through linear regression analysis showed strong correlation with standard instruments (R² = 0.94 for salinity and R² = 0.93 for turbidity). Field trials demonstrated effective maintenance of turbidity within 22-27 NTU for 24 hours, and stepwise tests confirmed the system’s ability to track real-time salinity shifts. These results indicate that the microcontroller-based system effectively stabilises key water parameters for H. nehereus aquaculture and performs more efficiently than open systems. As one of the first integrated systems designed for automated salinity and turbidity regulation in estuarine aquaculture, it offers a practical and scalable approach to improve sustainability and ensure the food security of coastal fisheries. Future work should extend control to pH, DO, and temperature, refine calibration with predictive algorithms and wireless connectivity so that it can be used more widely in precision aquaculture with fish stocks.